THE EVALUATION OF SAM RATULANGI INTERNATIONAL AIRPORT ATTRIBUTES BY USING IMPORTANCE AND PERFORMANCE ANALYSIS - Kotangon, Armando Andika; Pangemanan, Sifrid S.; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Nowadays transportation is a very important tool in human life. The needs to move and to distribute goods makes transportation much needed. Moving and distribution of the goods is very important because this is what makes the economy run. The objectives of this research are to know about the importance and performance of Sam Ratulangi International Airport Attributes. This research is descriptive study with a quantitative approach. Descriptive in this study means that the researcher tries to describe and explain the airport attributes of Sam Ratulangi International Airport by using Importance and Performance Analysis. 100 Respondents are the sample size of this research. The result of this research shows that Resting Facilities are located in quadrant I which is very importance for consumer but the performance perceived to be low. Parking Facilities and Airport Image are located in quadrant II because it is importance for consumer meanwhile the performance also is good. These attributes are the biggest factor that influence The Airport. Whereas for Luggage Handling and Commercial Facilities are in quadrant III means that the two attributes are not really importance for the consumer and at the same time also has the low performance level. Sam Ratulangi International Airport better to pay more attention and improve the attributes that have low performance and maintain the attributes that has high performance to get better. Keywords: importance and performance analysis, airport attributes